1998
DOI: 10.1093/emboj/17.9.2543
|View full text |Cite
|
Sign up to set email alerts
|

The Ssn6-Tup1 repressor complex of Saccharomyces cerevisiae is involved in the osmotic induction of HOG-dependent and -independent genes

Abstract: The response of yeast to osmotic stress has been proposed to rely on the HOG-MAP kinase signalling pathway and on transcriptional activation mediated by STRE promoter elements. However, the osmotic induction of HAL1, an important determinant of salt tolerance, is HOG independent and occurs through the release of transcriptional repression. We have identified an upstream repressing sequence in HAL1 promoter (URS HAL1 ) located between -231 and -156. This promoter region was able to repress transcription from a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
62
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(67 citation statements)
references
References 62 publications
5
62
0
Order By: Relevance
“…The regulation of HAL1 gene expression has been previously reported to depend on a repression mechanism occurring on an upstream promoter region, URS HAL1 (Ϫ231 to Ϫ156) (23). A database search (MatInspector 34) revealed a CRE-like sequence at position Ϫ222 to Ϫ215.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The regulation of HAL1 gene expression has been previously reported to depend on a repression mechanism occurring on an upstream promoter region, URS HAL1 (Ϫ231 to Ϫ156) (23). A database search (MatInspector 34) revealed a CRE-like sequence at position Ϫ222 to Ϫ215.…”
Section: Resultsmentioning
confidence: 99%
“…The GST-Sko1 fusion protein was tested for CRE HAL1 interaction as described previously (33). Binding conditions for His-tagged Gcn4 protein and general conditions of electrophoresis were as described previously (23). Yeast protein extracts were prepared as in reference (23).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Network analysis of these regulators showed that many regulators are highly connected and interact with each other genetically and biochemically ( Fig. 8) (5,18,44,59,72,80,81,88,91,95,98,106,120,123,128). Many of the regulators are components of global regulatory complexes.…”
Section: Suppression Of Hypoxia Responsiveness Of a Network Of Regulamentioning
confidence: 99%
“…Total RNA was isolated according to Carlson and Botstein (1982) and Northern blot analysis was performed as described by Má rquez et al (1998). The probes used were PCR fragments spanning the whole CTT1 and HAL2 ORFs or part of the NST1 ORF.…”
Section: Northern Blot Analysismentioning
confidence: 99%